Prenatal testing - diagnostic possibilities in the 21st century with special emphasis on the diagnosis of genetic defects and heart defects - Grzegorz Tarsa; Rami Ben Rhaiem; Katarzyna Sudelska; Zuzanna Sawińska; Przemysław Kępka; Aleksandra Łokczewska-Bojar; Daria Kuziemkowska; Jan Kuźma; Magdalena Skotalczyk; Anna Łącka-Majcher (Journal of Education, Health and Sport, 2023)
Introduction: Prenatal diagnosis is a branch of medicine that deals with the detection of possible genetic and developmental abnormalities at the fetal life stage. Due to the rapid development of technology in recent decades, diagnostic capabilities at the prenatal stage have also changed their face.